2016
DOI: 10.1177/1471301216642900
|View full text |Cite
|
Sign up to set email alerts
|

Care to talk? A framework for appreciative conversations about dementia: Innovative practice

Abstract: When people with dementia are admitted to hospital, both they and their carers and families have crucial roles to play. They should be positioned as the only true experts in the unique individuality of the person and brought into the nursing process as an equal partner in care. 'Care to Talk' is a conversational model developed through Appreciative Inquiry to facilitate this way of working. The model, its development and outcomes are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Thirteen studies reported behaviour change of staff,4 8 9 20 21 23 24 28 32 34 36–38 41 43 44 49 50 including three in a quantitative way 20 21 23 41. The highest quality study was a controlled study, which showed no change in pain score of the patients 20 21.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirteen studies reported behaviour change of staff,4 8 9 20 21 23 24 28 32 34 36–38 41 43 44 49 50 including three in a quantitative way 20 21 23 41. The highest quality study was a controlled study, which showed no change in pain score of the patients 20 21.…”
Section: Resultsmentioning
confidence: 99%
“…One reported 92% of commitments to change were implemented 36. Five studies observed that staff changed their interactions with patients 24 36 43–45 49 50. Examples of this include nurses increasing the frequency and consistency of oral care in a rehabilitation hospital36 and nurses doing hourly rounding to ensure patient’s needs (eg, toileting and comfort) are met 49.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One ward has piloted using mapping outcomes as a new approach for assessment, care and treatment planning focusing on the individual and including his or her family/carer (we reported the broader aspects of this, see Page, Rowett, & Davies-Abbott, 2016). When a person is admitted to the ward several mapping sessions (of around one to three hours) are completed in the first week.…”
Section: Mapping As Assessmentmentioning
confidence: 99%
“…Given the widespread concerns about the quality of care received by people with dementia in hospital settings (Ashton & Manthorpe, 2017; de Vries, Drury-Ruddlesden, & Gaul, 2016), there is a clear rationale for testing Appreciative Inquiry in this setting. In the second article, Page, Rowett, and Davies-Abbott (2017) explain how Appreciative Inquiry was used to develop the Care to Talk model in Wales to encourage open and honest conversations between health professionals, people with dementia and family caregivers.…”
mentioning
confidence: 99%